Hydroalcoholic Extract of Cuscuta Epithymum Enhances Pentobarbitalinduced Sleep: Possible Involvement of GABAergic System - Forouzanfar, Fatemeh; Vahedi, Mohammad M.; Aghaei, Azita; Rakhshandeh, Hassan (Current Drug Discovery Technologies, 2020)
Background: Insomnia is the most common sleep disorder. The present study was undertaken to evaluate the sedative-hypnotic potential of hydroalcoholic extract (HAE) of Cuscuta epithymum and its fractions. Method: HAE and its fractions including: water fraction (WF), ethyl acetate fraction (EAF) and n-hexan fraction (NHF) were i.p administered to male mice and 30 min later pentobarbital (30 mg/kg, i.p.) was injected to induce sleep. Then the latent period and continuous sleeping time were recorded. Besides, 30 mins after administration of HAE motor coordination (rota-rod test) were assessed. Additionally, LD50 of HAE was determined and the possible neurotoxicity of the extract was tested on neural PC12 cells. Results: The HAE and NHF decreased the latency of sleep and significantly increased the duration of sleep induced by pentobarbital. These effects of C. epithymum were reversed by flumazenil. HAE did not affect the animals’ performance on the rotarod test. The LD50 value for HAE was found to be 4.8 g/kg. HAE and its fractions had no toxicity effect on the viability of PC12-cell line. Conclusion: The results of the present study indicate that the HAE and NHF have significant sedativehypnotic effects in mice without major toxic effect and that the benzodiazepine receptors are involved in the sedative-hypnotic effects of this plant.
Keywords: diazepam